Perspectives on Collector Collaboration: The Northern Arizona Paleoindian Project. Issue 1 (February 2022) - Rowe, Matthew J.; Adams, E. Charles; Clark, Dan; Cundiff, Ricky; Bailey, Kassi Sue; Soza, Danielle R.
Abstract: In 2019, we launched the Northern Arizona Paleoindian Project to expand on findings from the Rock Art Ranch (RAR) Research Experiences for Undergraduates (REU; NSF#1262184). The REU recovered 24 Paleoindian artifacts in association with drainages. Expansion of the research required mitigation of the patchwork landownership in the area, which encouraged a collector-collaboration model following Pitblado (2014 ) and Douglass et alia (2017 ). We held public events in collaboration with a network of agencies, avocational groups, collectors, and landowners to assess potential for Paleoindian archaeology in the area. In March 2020, however, the COVID-19 pandemic halted our efforts, allowing us to evaluate our project and practice. We find that tapping into existing local networks of responsible resource stewards (RRS) can greatly accelerate project development. We also find that private collections are endangered, and preserving this portion of the archaeological record requires documentation and long-term curation. Most importantly, we find that archaeologists working with collectors are uniquely positioned to build bridges between Indigenous communities, RRS, and professional archaeologists to help stabilize legacy collections and that this focus should drive collector-collaboration research design. Ultimately, the project must move toward a community-based participatory research design to seek equitable and culturally appropriate curation plans for local legacy collections.